2019
DOI: 10.21037/atm.2019.04.76
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and clinical outcomes of cervical cancer during pregnancy

Abstract: Background: This study aims to investigate clinicopathological factors associated with survival rate and treatment of patients with cervical cancer during pregnancy (CCP). Methods: A total of 92 patients diagnosed CCP were retrospectively reviewed. One patient was from Nanfang Hospital of Southern Medical University, 5 patients were from Tongji Hospital, and 86 patients were from case reports in the PubMed database from 1961 to 2019. Patients and tumor characteristics were evaluated. Kaplan-Meier and Cox regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…This was taken to indicate that continuation of the pregnancy did not adversely affect maternal oncologic treatment. In contrast, other studies have reported that delayed treatment did aggravate tumor progression, with higher mortality rates and disease recurrences [ 19 , 20 ]. However, in these studies, the clinical features (such as clinical stage, tumor size, lymph node metastasis) were not compared between the continuation of pregnancy group and the termination of pregnancy group.…”
Section: Discussionmentioning
confidence: 86%
“…This was taken to indicate that continuation of the pregnancy did not adversely affect maternal oncologic treatment. In contrast, other studies have reported that delayed treatment did aggravate tumor progression, with higher mortality rates and disease recurrences [ 19 , 20 ]. However, in these studies, the clinical features (such as clinical stage, tumor size, lymph node metastasis) were not compared between the continuation of pregnancy group and the termination of pregnancy group.…”
Section: Discussionmentioning
confidence: 86%
“…7 Study shows the 5 years disease specific survival for delayed treatment is 61%, whereas for the immediate action is 86%. 10 Administration of NACT can help to control the tumor progression. NACT has been applied in a case of 21 weeks pregnant woman with cervical carcinoma FIGO stage IB1 in China, who wanted to continue the pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Obstetrics, neonatology, gynecological oncology, pathology, imaging, and other disciplines need to participate in formulating treatment plans. Strike a balance between effective treatment of tumors and protection of fetal health to avoid delayed treatment and premature delivery ( 10 , 11 ). For details, please refer to the Chinese Expert Consensus on Diagnosis and Treatment of Pregnancy Complicated with Cervical Cancer, formulated by the Chinese Obstetricians and Gynecologists Association (COGA) ( 11 ).…”
Section: Multidisciplinary Diagnosis and Treatment In Ccipmentioning
confidence: 99%